Gemcitabine and Antisense-microRNA Co-encapsulated PLGA-PEG Polymer Nanoparticles for Hepatocellular Carcinoma Therapy - Devulapally, Rammohan (ACS Appl Mater Interfaces, 2016)
Hepatocellular carcinoma (HCC) is highly prevalent, and the third most common cause of cancer-associated deaths worldwide. HCC tumors respond poorly to chemotherapeutic anticancer agents due to inherent and acquired drug resistance, and low drug permeability. Targeted drug delivery systems with significant improvement in therapeutic efficiency are needed for successful HCC therapy. Here, we report the results of a technique optimized for the synthesis and formulation of antisense-miRNA-21 and gemcitabine (GEM) co-encapsulated PEGylated-PLGA nanoparticles (NPs) and their in vitro therapeutic efficacy in human HCC (Hep3B and HepG2) cells. Water-in-oil-in-water (w/o/ w) double emulsion method was used to coload antisense-miRNA-21 and GEM in PEGylated-PLGA-NPs. The cellular uptake of NPs displayed time dependent increase of NPs concentration inside the cells. Cell viability analyses in HCC (Hep3B and HepG2) cells treated with antisense-miRNA-21 and GEM co-encapsulated NPs demonstrated a nanoparticle concentration dependent decrease in cell proliferation, and the maximum therapeutic efficiency was attained in cells treated with nanoparticles co-encapsulated with antisense-miRNA-21 and GEM. Flow cytometry analysis showed that control NPs and antisense-miRNA-21-loaded NPs are not cytotoxic to both HCC cell lines, whereas treatment with free GEM and GEM-loaded NPs resulted in ~9% and ~15% apoptosis, respectively. Cell cycle status analysis of both cell lines treated with free GEM or NPs loaded with GEM or antisense-miRNA-21 displayed a significant cell cycle arrest at the S-phase. Cellular pathway analysis indicated that Bcl2 expression was significantly upregulated in GEM treated cells, and as expected, PTEN expression was noticeably upregulated in cells treated with antisense-miRNA-21. In summary, we successfully synthesized PEGylated-PLGA nanoparticles co- encapsulated with antisense-miRNA-21 and GEM. These co-encapsulated nanoparticles revealed increased treatment efficacy in HCC cells, compared to cells treated with either antisense-miRNA-21- or GEM-loaded NPs at equal concentration, indicating that down-regulation of endogenous miRNA-21 function can reduce HCC cell viability and proliferation in response to GEM treatment.